A Subject in Allegorical Clothing: The Case of ‘el maldiciente Clodio’ in Los trabajos de Persiles y Sigismunda - McCallister, Timothy A. (Revista Canadiense de Estudios Hispánicos, 2021)
This article considers the relationship between allegorical personification and literary subjectivity in Miguel de Cervantes’s Los trabajos de Persiles y Sigismunda (1617). Although previous scholarship has recognized the allegorical qualities of the character Clodio, a slanderer par excellence, these qualities have been seen as incompatible with his marked inner life. I begin by clarifying the understanding of speech vices in seventeenth-century Spain as a single vice measured by speech’s harmful effect. I then draw from philosophical and psychological studies on self-knowledge to argue that Clodio’s subjectivity is a function of his allegorical nature. His status as a personification of the speech vices gives rise to the introspection and agency that characterize him.